2018
DOI: 10.4103/aian.aian_86_18
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial atherosclerosis is the most common stroke subtype: Ten-year data from hyderabad stroke registry (India)

Abstract: Aim:Limited data regarding stroke subtypes exist from South Asian countries. The aim of the study was to determine the pattern of ischemic stroke subtypes and their associated risk factors, in a 10-year long hospital-based registry in the South Indian city of Hyderabad.Materials and Methods:The Hyderabad stroke registry systematically collected clinical, radiological, and laboratory data of fully investigated consecutive stroke patients and studied pattern of ischemic stroke subtypes and their risk factor asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…Embolic strokes due to emboli originating from the heart or extracranial large arteries are common in Western populations, whereas small-vessel occlusion or intracranial atherosclerosis is more prevalent in Asians [ 23 ]. Whites have more extracranial carotid atherosclerosis [ 20 , 24 ], whereas Asians have more intracranial atherosclerotic disease [ 22 , 25 , 26 ]; 54% of ethnic South Asians living in Singapore [ 27 ] and 29.4% of Indian patients in the Hyderabad stroke registry [ 28 ] were reported to have intracranial large-artery disease. Among ischaemic stroke subtypes, lacunar strokes, which were once the commonest variety in Asians, are now declining.…”
Section: Discussionmentioning
confidence: 99%
“…Embolic strokes due to emboli originating from the heart or extracranial large arteries are common in Western populations, whereas small-vessel occlusion or intracranial atherosclerosis is more prevalent in Asians [ 23 ]. Whites have more extracranial carotid atherosclerosis [ 20 , 24 ], whereas Asians have more intracranial atherosclerotic disease [ 22 , 25 , 26 ]; 54% of ethnic South Asians living in Singapore [ 27 ] and 29.4% of Indian patients in the Hyderabad stroke registry [ 28 ] were reported to have intracranial large-artery disease. Among ischaemic stroke subtypes, lacunar strokes, which were once the commonest variety in Asians, are now declining.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted association of ICAD with hyperlipidemia in LAA and those cardioembolic strokes. (19) From our data those with large artery strokes had higher and those with lacunar infarcts had lower occurrence of ICAD.…”
Section: Discussionmentioning
confidence: 46%
“…Although the association of hyperlipidemia with ICAD has been demonstrated from past studies (8,19,20), the APAC study concluded that triglycerides (TG) are a signi cant factor only for progression of atherosclerosis, (21) another study concluded TG: HDL cholesterol ratio to be signi cantly associated with ICAD in healthy subjects. (22) We noted that ICAD was signi cantly associated in those with previous history of hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Intizari 7 on 1,158 patients with hemispheric stroke, 493 (42.5%) had features of lacunar stroke which is similar to our study. An analysis done on 893 patients of ischemic stroke in the stroke registry of Nizam's Institute of Medical Sciences, Hyderabad, 8 showed 16% of stroke patients with lacunar infarction. In contrast to our results, a study conducted on stroke in south Alabama, 9 lacunar infarct composed of 13% of stroke patients.…”
Section: Discussionmentioning
confidence: 99%